Comparative in silico analyses between Lactiplantibacillus plantarum and Bifidobacterium longum concerning probiotic properties, anti-lipidemic, and anti-diabetic in vitro activities - Asmaa Negm El-Dein; Wafa A. Alshehri; Ashjan F. Khalel; Hassan M. Awad (BMC Microbiology)
Abstract The gut microbiota plays a crucial role in gastrointestinal health, immune function, and overall well-being. Dysbiosis has been linked to various conditions such as colon cancer, atopic diseases, mental disorders, autoimmune disorders, obesity, and diabetes. This in vitro study aims to assess the safety and functional potential of two probiotic strains, Lactiplantibacillus (L) plantarum and Bifidobacterium (B) longum, focusing on their anti-lipidemic, anti-diabetic, antioxidant, and probiotic properties. The strains were tested for stress tolerance, including acidic, alkaline, osmotic, oxidative, thermal, detergent, bile salt, and pancreatic enzyme conditions. Both strains exhibited strong resilience, often surpassing the control strain. Their antioxidant activity, measured by radical scavenging ability, was comparable to ascorbic acid, with values of 77% for L. plantarum and 92% for B. longum. Cholesterol-lowering capacity reached 50% and 49% after 3 days, increasing to 59% and 78% after 7 days, respectively. Hydrophobicity, an indicator of adhesion potential, was approximately 78% for L. plantarum and 80% for B. longum. Additionally, both strains showed low α-amylase activity (91.65 and 92.33 U/ml), suggesting a potential role in slowing carbohydrate digestion and managing blood glucose levels. Overall, the strains demonstrated favorable safety profiles and promising functional attributes for alleviating hyperlipidemia and diabetes. PCA and heatmap analyses further highlighted L. plantarum as the most promising candidate.